Multiphysics Modeling and Simulation of the Behavior of Cemented Tailings Backfill - Cui, Liang (Université d'Ottawa / University of Ottawa, 2017)
One of the most novel technologies developed in the past few decades is to convert mine wastes into cemented construction materials, otherwise known as cemented tailings backfill (CTB). CTB is an engineered mixture of tailings (waste aggregates), water and hydraulic binders. It is extensively used worldwide to stabilize underground cavities created by mining operations and maximize the recovery of ore from pillars. Moreover, the application of CTB is also an environmentally friendly means of disposing potential acid generating tailings underground. During and after its placement into underground mine excavations or stopes, complex multiphysics processes (including thermal, T, hydraulic, H, mechanical, M, and chemical, C, processes) take place in the CTB mass and thus control its behavior and performance. With the interaction of the multiphysics processes, the field variables (temperature, pore water pressure, stress and strain) and geotechnical properties of CTB undergo substantial changes. Therefore, the prediction of the field performance of CTB structures during their life time, which has great practical importance, must incorporate these THMC processes. Moreover, the self-weight effect, water drainage through barricades, thermal expansion and chemical shrinkage can contribute to the volumetric deformation of CTB. Consequently, CTB exhibits unique consolidation behavior compared to conventional geomaterials (e.g., soil). Furthermore, the consolidation processes can result in relative displacement between the rock mass and CTB. The resultant rock mass/CTB interface resistance can reduce the effects of the overburden pressure or the vertical stress (i.e., arching effect). Hence, a full understanding, through multiphysics modeling and simulation of CTB behaviors, is crucial to reliably assess and predict the performance of CTB structures. Yet, there are currently no models or tools to predict the fully coupled multiphysics behavior of CTB. In this Ph.D. study, a series of mathematical models which include an evolutive elastoplastic model, a fully coupled THMC model, a multiphysics model of consolidation behavior and a multiphysics model of the interaction between the rock mass/CTB interface are developed and validated. There is excellent agreement between the modeled results and experimental and/or in-situ monitored data, which proves the accuracy and predictive ability of the developed models. Furthermore, the validated multiphysics models are applied to a series of engineering issues, which are relevant for the field design of CTB structures, to investigate the self-desiccation process, consolidation behavior of CTB structures as well as to assess the pressure on barricades and the strength development in CTB structures. The obtained results show that CTB has different behaviors and performances under different backfilling conditions and design strategies, and the developed multiphysics models can accurately model CTB field behavior. Therefore, the research conducted in this Ph.D. study provides useful tools and technical information for the optimal design of CTB structures.
Keywords: Cemented paste backfill; Tailings; THMC; Multiphysics; Coupling processes; Mine